Studija presjeka propisivačkih navika za antimikrobne agense među hospitalizovanim pacijentima internog odjeljenja tercijernog zdravstvenog centra - Jain, Monica; Kakkar, Shivankan; Bansal, Alka; Kapadia, Rupa (Scripta Medica, 2020)
Background: Antimicrobial agents are the mainstay of treatment in modern medicine. In view of emerging threat of Antimicrobial Resistance (AMR), there was a requirement aimed at identifying patterns of antimicrobial prescribing. The prescribing pattern of antimicrobial agents (AMAs) among the medicine inpatients of SMS Medical College & Hospital, Jaipur, India was studied. The objectives were to evaluate, monitor and suggest rational prescribing practices.Methods: This was a cross-sectional study that was done for a period of one year from July 2016 to June 2017. The rationality of antimicrobial drug use was evaluated by analysing the prescriptions.Results: A total of 400 patients were included in the study. Percentage of indoor patients with one or more AMAs prescribed was 48.75 %. The average number of AMAs prescribed was 1.67. Percentage of AMAs prescribed consistent with the National List of Essentials Medicines (NLEM) was 89.73 %. The average AMAs duration prescribed was found to be 4.24 days. The most commonly prescribed antibacterial agent in medicine in patients was a beta-lactam AMA with 57.29 % of all prescriptions.Conclusion: AMR is strongly linked to improper antimicrobial use. This study suggests that certain interventions are required to minimise toxicity and lessen the chances of emergence of resistance. It is therefore proposed that there should be continuous education on rational use of drugs among healthcare professionals.
Keywords: Antiinfektivni agensi; Mikrobna rezistencija; Esencijalna lista lekova; Programi za praćenje lekova na recept